Hypertrophic cardiomyopathy in neonates with congenital hyperinsulinism. Issue 4 (1st February 2013) - Huang, TingTing; Kelly, Andrea; Becker, Susan A; Cohen, Meryl S; Stanley, Charles A
Abstract : Introduction: Hypertrophic cardiomyopathy (HCM) is a well-recognised complication in infants of diabetic mothers and is attributed to a compensatory increase in fetal insulin secretion. Infants with congenital hyperinsulinism have excessive prenatal and postnatal insulin secretion due to defects in pathways of insulin secretion (most commonly the KATP channel). HCM has been reported in a few neonates with hyperinsulinism, but its extent and risk factors for its development have not been evaluated. Methods: Retrospective chart review of infants, age <3 months, with congenital hyperinsulinism managed by Children's Hospital of Philadelphia over a 3.5-year period. Data: Gestational age, birth weight, hyperinsulinism form and treatments, echocardiogram results, cardiac/respiratory complications. Results: 68 infants were included, 58 requiring pancreatectomy for diffuse (n=28) or focal (n=30) disease, 10 were diazoxide-sensitive. Twenty-five had echocardiograms performed. Ten had HCM, all of whom required pancreatectomy and eight of whom had confirmed ATP-sensitive potassium-hyperinsulinism. Subjects with HCM had younger gestational age 36(32, 38) than their surgical counterparts without HCM 38 (31.6, 43), p=0.02. Discussion: HCM appears common in infants with severe hyperinsulinism. Routine echocardiogram and EKG of at-risk newborns should be considered. Fetal hyperinsulinism is the likely mediating factor for HCM in HI infants.